Extent and Predictors of Decision Regret about Health Care Decisions: A Systematic Review. (August 2016) - Becerra Pérez, Maria Margarita; Menear, Matthew; Brehaut, Jamie C.; Légaré, France
Background. People often face difficult decisions about their health and may later regret the choice that they made. However, little is known about the extent of decision regret in health care or its predictors. We systematically reviewed evidence about the extent of decision regret and its risk factors among individuals making health decisions.Methods. The data sources were Medline, Embase, and reverse citation searches in Google Scholar and Web of Science. Studies using the Decision Regret Scale (DRS) to measure decision regret among individuals making nonhypothetical health decisions were included. There were no restrictions on study design, setting, or language. We extracted characteristics of included studies, measures of central tendency for DRS scores (0 = no regret, 100 = high regret), and all risk factors from published analyses. Quality appraisal was conducted using the Mixed Methods Appraisal Tool. A narrative synthesis was performed owing to the heterogeneity of studies.Results. The initial search yielded 372 unique titles, and 59 studies were included. The overall mean DRS score across studies was 16.5, and the median of the mean scores was 14.3 (standard deviation range = 2.2–34.5) ( n = 44 studies). The risk factors most frequently reported to be associated with decision regret in multivariate analyses included higher decisional conflict, lower satisfaction with the decision, adverse physical health outcomes, and greater anxiety levels.Conclusions. The extent of decision regret as assessed with the DRS in nonhypothetical health decisions was often low but reached high levels for some decisions. Several risk factors related to the decision-making process significantly predicted decision regret. Additional research into the psychometrics of the DRS and the relevance of scores for clinicians and patients would increase the validity of decision regret as a patient-reported outcome.